Association between UCP1, UCP2, and UCP3 gene polymorphisms with markers of adiposity in European adolescents: The HELENA study. Issue 6 (18th January 2019) - Pascual‐Gamarra, Jose Miguel; Salazar‐Tortosa, Diego; Martinez‐Tellez, Borja; Labayen, Idoia; Rupérez, Azahara I.; Censi, Laura; Manios, Yannis; Nova, Esther; Gesteiro, Eva; Moreno, Luis A.; Meirhaeghe, Aline; Ruiz, Jonatan R.
Summary: Aims: To examine the association between UCP1, UCP2, and UCP3 gene polymorphisms with adiposity markers in European adolescents and to test if there were gene interactions with objectively measured physical activity and adiposity. Methods: A cross‐sectional study that involves 1.057 European adolescents (12‐18 years old) from the Healthy Lifestyle in Europe by Nutrition in Adolescence Cross‐Sectional Study. A total of 18 polymorphisms in UCP1, UCP2, and UCP3 genes were genotyped. We measured weight, height, waist, and hip circumferences and triceps and subscapular skinfold thickness. Physical activity was objectively measured by accelerometry during 7 days. Results: The C allele of the UCP1 rs6536991 polymorphism was associated with a lower risk of overweight (odds ratio [OR]: T/C + C/C vs T/T) = 0.72; 95% confidence interval [CI]: 0.53‐0.98; P = 0.034; false discovery rate [FDR] = 0.048). There was a significant interaction between UCP1 rs2071415 polymorphism and physical activity with waist‐to‐hip ratio ( P = 0.006; FDR = 0.026). Adolescents who did not meet the physical activity recommendations (less than 60 min/day of moderate to vigorous physical activity) and carrying the C/C genotype had higher waist‐to‐hip ratio (+ 0.067; 95% CI, 0.028‐0.106; P = 0.003), while no differences across genotypes were observed in adolescents meeting the recommendations. Conclusions: Two UCP1 polymorphisms were associated with adiposity in European adolescents. Meeting the daily physical activity recommendations may overcome the effect of the UCP1 rs2071415 polymorphism on obesity‐related traits.